Menstrual disorders following COVID-19 vaccination: a review using a systematic search - Smaardijk, Veerle R.; Jajou, Rana; Kant, Agnes; van Hunsel, Florence P. A. M. (Frontiers in Drug Safety and Regulation, 2024)
Introduction:Menstrual disorders are commonly reported after COVID-19 vaccination and heavy menstrual bleeding was added to the product information of the COVID-19 vaccines of Moderna and Pfizer. The aim of this review, using a systematic search, is to provide an overview of available literature on the risk of menstrual disorders after COVID-19 vaccination. Methods: The review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. A PubMed search was performed on 15 August 2023, including solely quantitative studies in English and Dutch. Results: A total of 61 studies were included, of which 40 were cross-sectional studies, 18 cohort studies, and three self-controlled case series. Outcomes included a wide variety of menstrual disorders, including changes in cycle length (n = 54), changes in the amount of bleeding (n = 44), changes in menses length (n = 30), changes in the experience of (pre)menstrual pain (n = 21), and breakthrough bleeding (n = 18). All included studies found a higher percentage of at least one menstrual disorder in the first cycle after different types of COVID-19 vaccination and after different doses. Discussion: In conclusion, evidence suggests that COVID-19 vaccines may cause menstrual changes in women of reproductive age. However, there is a need for more longitudinal studies because of important limitations in the study designs of many of the included studies. Although menstrual changes are short-lived and predominantly mild, it is important for women and healthcare professionals to be informed about these potential adverse reactions and to assess these events in clinical trials on vaccines.